PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA LEAFLET TERHADAP PENGETAHUAN IBU TENTANG PENATALAKSANAAN ISPA PADA BALITA DI POSYANDU - Tina Yuli Fatmawati (Universitas Batanghari Jambi, 2017)
Acute respiratori infections have occurred in infant. Incidence of infants is estimated to be 0.29 episodes of role / year in developing countries and 0.05 episodes / year in developed countries. Most cases occur in India (43 Million), China (21 Million) and Pakistan (10 Million) and Bangladesh, Indonesia and Nigeria respectively 6 million Prevalence of ARI in infants in Indonesia as many as 25.0% with the highest characteristic occur in age group 1-4 years (25.8%). In Jambi , ISPA disease of 10 major diseases.This research is a pre experimental using One Group pretest-posttest design. This research was conducted at Posyandu Bambu Kuning Jambi. The population in this study amounted to 84 people with a sample of 20 respondents. Data analysis using univariate and bivariate analysis. The Result known that from 20 Respondents majority of respondents (60.0%) have good knowledge before given health education. After being given health education to 95.0% of respondents have good knowledge. The result of bivariate analysis shows that there is a significant influence between the knowledge of the respondents before and after being given health education with p-value = 0,00. It is hoped that the puskesmas is primarily responsible for posyandu or health promotion to give a continue and scheduled counseling to mothers especially those with toddlers so as to improve healthy life behavior especially in the prevention and management of ISPA.Keywords: Knowledge, Health education, ISPA in Infant